2016
DOI: 10.1177/0269215515622670
|View full text |Cite
|
Sign up to set email alerts
|

The effects of manual therapy or exercise therapy or both in people with hip osteoarthritis: a systematic review and meta-analysis

Abstract: An Exercise therapy intervention provides short-term as well as long-term benefits in terms of reduction in pain, and improvement in physical function among people with hip osteoarthritis. The observed magnitude of the treatment effect would be considered small to moderate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…This is achieved currently with a mixture of exercises to strengthen the muscles around the joint, stabilizing it and manual therapy to improve the mobility of the joint capsule and the surrounding tissue [40]. However, its use in the past has largely been based on expert consensus rather than a research base.…”
Section: Physical Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…This is achieved currently with a mixture of exercises to strengthen the muscles around the joint, stabilizing it and manual therapy to improve the mobility of the joint capsule and the surrounding tissue [40]. However, its use in the past has largely been based on expert consensus rather than a research base.…”
Section: Physical Therapymentioning
confidence: 99%
“…With regards to exercise therapy, while it was noted that there was a paucity of high-quality evidence over long-term periods, two reviews found that group classes or home exercises were effective at managing the pain associated with Hip OA [40,41]. One study found that a 12-week exercise programme, where patients performed exercises two to three times a week, reduced the need for THR by up to 44% [42].…”
Section: Physical Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, exercise therapy in a patient’s home is effective for gait ability and activities of daily living owing to improvement in joint stability, muscle strength, and range of motion [ 5 ]. Previous studies have demonstrated that hip osteoarthritis patients can experience improvements in their pain and physical function through exercise therapy [ 6 - 8 ], and that this therapy is more effective when it is conducted in a patient’s home rather than at a hospital [ 9 ]. Therefore, it is important to provide an effective home-exercise program that can be easily understood, that can be performed at home by patients, and that is adaptable to their individual symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Die Arbeit von Bennell et al[48] zum Thema Kniearthrose empfahlen allerdings mindestens 12 Einheiten unter Anleitung für mehr als 3-mal/Woche. Somit wird auch hier der Einfluss einer adäquaten Dauer der TT-Einheiten auf die Wirkung deutlich[49].Zudem finden sich in den Ergebnissen[23][24][25] und in der Literatur [5][50] Hinweise darauf, dass TT eine größere Wirkung auf das Evaluierungsparameter Funktion haben könnte. Studien [28][29] besteht daher hohe bis mäßige Evidenz für eine positive Wirkung von TT.…”
unclassified